Chiara Bottici, “Imaginal Politics. Images beyond Imagination and the Imaginary”, Columbia University Press, New York 2014 - Heritier, Paolo (Teoria e Critica della Regolazione Sociale / Theory and Criticism of Social Regulation, 2020)